2001
DOI: 10.1002/cyto.1069
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic hybridization study of nasal‐type NK/T‐cell lymphoma

Abstract: Background: Nasal-type NK/T-cell lymphoma is a rare type of non-Hodgkin's lymphoma. The genetic changes associated with pathogenesis have not been well defined. This study investigates the nonrandom genetic alteration of nasal-type NK/T-cell lymphoma. Methods: Nine cases were studied. Comparative genomic hybridization (CGH) was carried out using fresh tumor tissues of seven nasal-type NK/T-cell lymphomas. To complement the data by CGH, loss of heterozygosity (LOH) of chromosomes 6q, 1p, and 17p using polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 23 publications
3
45
0
1
Order By: Relevance
“…Del 6q was the most frequent loss as in earlier studies 4,6,8 and four distinct regions: 6q21, 6q23.2, 6q25.3 and 6q26 have been suggested. 7,10,11,21,39 Previous results and our data suggest that 6q21 (B105.6-107 Mb) is the most common aberrant region (Table 1a).…”
Section: Genomic Studies On Natural Killer-cell Malignancies J Iqbal supporting
confidence: 61%
See 3 more Smart Citations
“…Del 6q was the most frequent loss as in earlier studies 4,6,8 and four distinct regions: 6q21, 6q23.2, 6q25.3 and 6q26 have been suggested. 7,10,11,21,39 Previous results and our data suggest that 6q21 (B105.6-107 Mb) is the most common aberrant region (Table 1a).…”
Section: Genomic Studies On Natural Killer-cell Malignancies J Iqbal supporting
confidence: 61%
“…6 We did not attempt to divide our cases into subcategories of NK-cell malignancies due to the small number of samples, but instead focused on abnormalities that are commonly present and probably important in the pathogenesis of NK-cell malignancies. Consolidating data from other studies 4,6,8 points to gains in 1q, 7q35, 17q21.2 and 20q11.1 are the most frequent. We examined the expression of 41000 transcripts residing in these regions and found that generally 30-50% of genes in these aberrant regions showed increase in expression compared with cases without the gains.…”
Section: Genomic Studies On Natural Killer-cell Malignancies J Iqbal mentioning
confidence: 89%
See 2 more Smart Citations
“…Amplification at 13q21-qter has been reported in diffuse large B-cell lymphoma (DLBCL; Ref. 5), mantle cell lymphoma (6), follicular lymphoma (7), primary cutaneous B-cell lymphoma (8), and nasal-type natural killer/T-cell lymphoma (9). Additional cases of amplification at 13q21-qter have also been reported in solid tumors: glioma (10), non-small cell lung cancer (10), bladder cancer (10), squamous-cell carcinoma of the head and neck (10), peripheral nerve sheath tumor (11), malignant fibrous histiocytoma (12), and alveolar rhabdomyosarcoma (13).…”
Section: Introductionmentioning
confidence: 99%